(untitled) - Nakayama, Kaneyoshi (Tokyo, 1993)
With its 500 photographs and illustrations, most of them in color, the book is an excelent visual guide to the culture, history and society of Japan. It is an easy-to-use reference to Japanese origins and myths, religions and rituals, traditions and festivals, architecture and art.